Surfer's Myelopathy: A Radiologic Study of 23 Cases - Beau K. Nakamoto; Andrea Siu; Kunitake Hashiba; Benjamin Sinclair; Bill Baker; Mark Gerber; Aaron McMurtray; Alison Pearce; J. Pearce (2013)
BACKGROUND AND PURPOSE: Surfing is an uncommon cause of an acute nontraumatic myelopathy. This study describes the MR imaging characteristics and clinical correlates in 23 subjects with surfer9s myelopathy. MATERIALS AND METHODS: This was a retrospective review of 23 cases of surfer9s myelopathy from 2003–2012. Spinal cord MR imaging characteristics and neurologic examinations with the use of the American Spinal Injury Association scale were reviewed. Logistic regression was used to determine associations between MR imaging characteristics, American Spinal Injury Association scale, and clinical improvement. RESULTS: All subjects (19 male, 4 female; mean age, 26.3 ± 7.4 years) demonstrated "pencil-like," central T2-hyperintense signal abnormalities in the spinal cord extending from the midthoracic region to the conus with associated cord expansion and varying degrees of conus enlargement on spinal cord MR imaging within 24 hours of symptom onset. T1 signal was normal. Faint gadolinium enhancement was present in a minority. Although there was a strong correlation between initial American Spinal Injury Association score and clinical improvement (P = .0032), MR imaging characteristics were not associated with American Spinal Injury Association score or clinical improvement. CONCLUSIONS: Surfer9s myelopathy should be considered in the radiographic differential diagnosis of a longitudinally extensive T2-hyperintense spinal cord lesion. MR imaging characteristics do not appear to be associated with severity on examination or clinical improvement.